Investigation of mammoth remains using the neutron activation analysis at the Training Reactor VR-1 - Stefanik, Milan; Sazelova, Sandra; Sklenka, Lubomir (Applied radiation and isotopes, 2020)
At the time when the importance of the interdisciplinary research increases, the nuclear analytical techniques supported by the small research reactors represent a useful tool for investigation of human society, culture, history etc. The historical, archaeological, and palaeontological samples and objects of cultural heritage can be easily studied using the radioanalytical methods such as the neutron activation analysis. This paper deals with the detailed investigation of fragments of mammoth remains from the Mid-Upper Palaeolithic site Pavlov VI by means of the instrumental neutron activation analysis at the Training Reactor VR-1 of the Czech Technical University in Prague. Six mammoth hard tissue samples (fragments of bones, tusk, and molar) from the Institute of Archaeology of the Czech Academy of Sciences were irradiated in the dry vertical irradiation channel with thermal neutron field (φ=2×109cm-2s-1) at maximum reactor power (80 W). The activated mammoth samples were analysed employing the nuclear γ-spectrometry and semiconductor HPGe detector, and the composition of the remains was determined (qualitative and quantitative analysis). The presence of Na, Cl, K, As, Fe, Sr, Mn, Br, I, Ba, and U was revealed in studied mammoth samples. Based on obtained production rates, the concentrations of Fe, Sr, Na, K, As, and U were determined. The results presented in this paper show clearly that the low-power Training Reactor VR-1 is excellent tool for the neutron activation analysis experiments within the interdisciplinary research and can provide experimental data important for archaeologists and palaeontologists.
Keywords: prvky; mamuti; paleontologie; Metals; Radioanalytical method; Czech Republic; Faunal remains; Gamma-ray spectroscopy; Fossils; Late pleistocene; Nuclear Reactors; Spectrometry, Gamma; Česká republika; zkameněliny; Mammoths; Production rate; radionuklidy; Neutron activation technique; Animals; kovy; Radioisotopes; Neutron Activation Analysis; Elements; neutronová aktivační analýza; Palaeontological samples; Gravettian; Paleontology; spektrometrie gama; atomové reaktory; zvířata; Nuclear reactor